Comparing outcomes of cardiac rehabilitation : secondary prevention in whites and nonwhites - Masiak, Krista (My University, 2011)
Background: Cardiac rehabilitation is a clinical program which assists heart patients with managing their cardiovascular risk factors and reducing their risk for future cardiac events. Purpose: The first purpose of the study was to determine the percentages of whites and nonwhites who met secondary prevention goals, at baseline and discharge. The second purpose of the study was to compare changes in specific outcomes between whites and nonwhites from baseline to discharge. Methods: The subjects were phase II cardiac rehabilitation patients enrolled in the Wisconsin Cardiac Rehabilitation Outcomes Registry (WiCORE) database. Frequency and descriptive tests were used to determine what percentages of whites and nonwhites met the secondary goals. Chi Square and repeated measures ANOVA were used to test significant differences. Results: At cardiac rehabilitation completion, white and nonwhite subjects reduced their risk of heart disease through management of risk factors. However, a significantly greater number of white subjects increased their volume of exercise, had greater loss of BMI, greater loss of weight, and a large gain in SF36PH scores.
Keywords: Weight loss.; Exercise.; Health status indications -- statistics & numerical data -- United States.; Health status indicators -- United States -- Statistics.; Heart -- Diseases -- Prevention.; Heart -- Diseases -- Patients -- Rehabilitation.